Unilever brand share price decline in Indonesia due to brand boycott action related to the israeli-palestinian conflict in the perspective of islamic economic law - Erwinata, Christy Wahyuni; Swadjaja, Isma; Isnawati, Muridah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The Israeli-Hamas war has come to public attention due to acts of violence and genocide in Palestine, public condemnation pays special attention to stock prices and public buying interest in products supporting Israel, one of which is Unilever brand products. This study aims to determine the decline in stock prices before the Israeli military aggression and after the military aggression, namely on September 1, 2023, and November 1, 2023. This study used normative legal methods. The results showed that the Israeli-Hamas war had an impact on the decline in Unilever's brand share price. The Israeli-Hamas war has resulted in a decrease in interest in buying products supporting Israel. The researcher concluded that the military aggression of the Israeli-Hamas war and criticism of the Israeli genocide against Palestinians had a significant impact on several countries. To fight colonialism around the world and support Palestinian independence, solidarity movements were held in several countries. The public's response to the criticism has been to boycott goods made by pro-Israel companies, including Unilever.